Návrh založení hodinové školky - Baluchová, Jana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Tato diplomová práce se zabývá návrhem založení malého podniku, a to konkrétně návrhem založení hodinové školky. Nejprve bude popsána teoretická část obsahující základní pojmy a legislativní požadavky. Dále bude zpracována analýza současného stavu podnikatelského sektoru a poté samotný podnikatelský plán s podrobným finančním plánem a harmonogramem řešení.

The goal of the thesis is concentrated on a proposal of creating a small business – namely by-the-hour kindergarten. The first part of the thesis describes theoretical ground, basic concepts and legal requirements. The next part contains analysis of the current situation of the business sector, followed by the actual business plan along with detailed financial plan and schedule.
Proposal of Creating a By-the-hour Kindergarten
Keywords: Založení podniku; podnikatelský plán; hodinová školka; finanční plán; Foundation of the company; business plan; by-the-hour kindergarten; financial plan